Invigorating Globalized EFL Learners’ Reading Proficiency Growth through the Continual Support of Multimodal Strategy - Kristian Florensio Wijaya (Journal of English Language and Pedagogy (JELPA), 2024)
As globalized EFL learners often elude themselves from participating in the designated reading learning activities prepared by their teachers due to the inevitable complexities, satiation, and frustration climates, the sustainable integration of a multimodal strategy is deemed as one of the essential digital learning approaches rewarding to be actualized by nowadays second language reading instructors. Previous researchers vehemently contended that with the support of a multimodal strategy, worldwide EFL learners no longer experience unpleasant reading learning climates since they interact with their digital texts enjoyably and meaningfully. This current small-scale library study is an actualization of the researcher's motivation to specifically reveal whether internalization of a multimodal strategy can reinforce globalized EFL learners' reading proficiency levels. To this end, the researcher employed a thematic analysis method in analyzing the specifically generated research results derived from 20 prior multimodal strategy scientific articles. To ascertain the credibility and relevancy of each analyzed research result, the researcher selected 20 already-published multimodal strategy articles ranging from 2018 until 2023. The thematically categorized research results highly advocated globalized second language reading instructors to arm language learners with the proper usage of a multimodal strategy to consistently promote more transformative reading learning enterprises in which EFL learners' targeted reading proficiency development can thrive to a greater level.